Desarrollo de un software educativo como apoyo didáctico en la asignatura de matemática para los alumnos del Tercer Año de EGB de la unidad educativa Iberoamericano de la ciudad de Loja, periodo 2013-2014 - Montaño Espinosa, Gabriela Soledad (2015)
This research has as its theme: “DEVELOPMENT OF AN EDUCATIONAL SOFTWARE TRAINING SUPPORT AS THE SUBJECT OF MATHEMATICS FOR THIRD YEAR STUDENTS OF EGB OF LATIN AMERICAN EDUCATIONAL UNIT Loja, PERIOD 2013-2014" The problem is It presents at all levels of education, where academic achievement in this area is very low, because it induces the study of the teaching-learning of mathematics that are hindering the crystallization and compliance with the integral formation of students. This problem is generated since the child starts his formal studies in the classroom and in the subject of mathematics, instead of often difficult for them to motivate their learning, causing a fear of numbers and logical-mathematical, is worse in subsequent grade levels, to the point where the student does not like to study mathematics, a situation that motivates for lost years and dropouts. Currently in the Latin-American Educational Unit, the situation becomes complex for the teaching-learning process as learning mathematics and traditionally taught by a passive student of the teaching process, giving little optimistic results for students Third Year Basic Education. The main objective was the creation and implementation of educational software for the subject of Mathematics Third Year of basic general education. To achieve the objectives the scientific, deductive, descriptive and statistical modeling methods were applied; Survey as well as technical and research instruments for data collection, with the participation of students and teachers of the school, verifying the lack of educational resources. The methodology used to build the application is named "Dynamic Educational Software Development Methodology". As a result of this research was conducted to 11 students of the third year of EGB and the teaching of the subject of Mathematics, 100% of respondents conclude that the educational software will support the teaching-learning process, and also They expressed that the themes of the Second Quimestre are more complex for students. In response, the educational software is developed with practical activities and multimedia content for strengthening the educational process, where the student can provide feedback and generate their own knowledge.